Ophiopogonin D′-induced mitophagy and mitochondrial damage are associated with dysregulation of the PINK1/Parkin signaling pathway in AC16 cells. (July 2022) - Lei, Sisi; Feng, Yuchao; Huang, Peiying; Chen, BoJun; Bao, Kun; Wu, Qihua; Zhang, Haobo; Huang, Xiaoyan
Abstract: Shenmai injection (SMI) is a patented traditional Chinese medicine that is extracted from Panax ginseng and Ophiopogon japonicus and is commonly used to treat cardiovascular diseases and tumors. The O. japonicus extract Ophiopogonin D′ (OPD') is highly cardiotoxic. Mitochondria are central to OPD'-induced cardiotoxicity, although the precise mechanisms remain unclear. Excessive mitophagy activation and mitochondrial dysfunction lead to apoptosis, and the PTEN-induced kinase 1(PINK1)/Parkin pathway is critical in regulating mitophagy and mitochondrial function. We investigated the role of the PINK1/Parkin pathway in OPD'-induced mitochondrial damage and cardiotoxicity in AC16 cells. Concentrations of 2 μM OPD' and above inhibited cardiomyocyte viability and increased lactate dehydrogenase (LDH) release in a concentration- and time-dependent manner. OPD' was toxic to cells and mitochondria and increased the rate of apoptosis, triggering pyknosis, decreasing mitochondrial membrane potential (MMP), and decreasing the protein expression of the biogenesis regulator peroxisome proliferator-activated receptor γ coactivator-1 alpha (PGC-1α). The increased ratio of microtubule-associated proteins 1 A/1B light chain 3B (LC3-II/LC3-I) in mitochondria indicated that OPD' induced mitophagy. OPD' significantly induced oxidative stress and apoptosis, including increased reactive oxygen species (ROS) generation and decreased nuclear factor erythroid-2 related factor 2 (Nrf2), heme oxygenase-1(HO-1), and B-cell lymphoma 2 (Bcl-2) protein expression. OPD' activated the PINK1/Parkin pathway and promoted PINK1/Parkin translocation to mitochondria. Inhibiting mitophagy attenuated OPD'-induced PINK1/Parkin pathway activation and preserved mitochondrial biogenesis, consequently mitigating OPD'-induced mitochondrial dysfunction and apoptosis. These findings suggest that OPD'-induced cardiomyocyte mitophagy and mitochondrial damage are at least partially mediated by dysregulation of the PINK1/Parkin pathway. Graphical Abstract: ga1 Highlights: Ophiopogonin D′ (OPD') causes mitochondrial damage and activates mitophagy. OPD' activates the PINK1/Parkin pathway leading to mitophagy. Inhibition of mitophagy provides cardioprotection against OPD'.